Democracia e participação social no âmbito das relações entre o estado e as organizações da sociedade civil : análise do contexto brasileiro pós marco regulatório - Reis, Patricia Lane Araújo (2021)
This thesis sought to understand the relational dynamics between Civil Society Organizations – CSOs and the State, from the perspective of strengthening social participation and democracy after the implementation of Law No. 13.019/2014. To enter this study, it was necessary to delve into the recent history of CSOs, demonstrating the need to create a Law that would guarantee transparency in the use of public resources and legal security for the segment of Civil Society Organizations and its implementation in the current situation of weakening institutions democracy and the advance of authoritarianism. The research was mediated by the dialectical-critical method, seeking to dialogue with contradictions, totality and historicity. To enrich the exposition of this study, both Marx and his critique of Capitalism, as well as Gramsci and his studies of the Extended State and Civil Society were essential. This is a qualitative research, which had as procedures used for data collection: document research, questionnaire application and semi-structured interview. Five subjects were interviewed and a questionnaire was applied to 34 research subjects, all subjects surveyed have in their trajectory connection with the objectives of this study. The discursive textual analysis technique was based on studies by Moraes (2003). At the end of the research, the thesis is reached that: the successive, contradictory and complex processes that shape Brazilian democracy and, in particular, the current post-regulatory framework had a direct impact on the relationship between the State and Civil Society Organizations (CSOs), aggravating the challenges of expanding the social participation of CSOs in the relationship with the State and the achievement of the objectives of legitimization and legal security of these entities, still prevailing a culture of bureaucratic criminalization and instrumentalization of CSOs as a neoliberal logic, limiting them to the role of implementing policies and substitutes for the State and not of partnerships with autonomy and legitimacy. These challenges mainly affect CSOs whose agenda is the defense of rights and strategic resources, hindering the formation of instances to strengthen the partnership, such as the Development and Collaboration Council (CONFOCO) or similar, to be instituted in cities and states. The articulations to strengthen this segment are taking place through the articulation of the CSOs themselves, in training within the forums and representative groups, which seek to expand knowledge about the Regulatory Framework of Civil Society Organizations (MROSC) in cities and states, in an educational process and training to strengthen this segment. Finally, the importance of Law No. 13019/2014 is highlighted, for CSOs in Brazil, as an initial motto in the consolidation of this social segment as part of networks of action and solidarity that guarantee and defend the rights of subalternized groups against the advance of state authoritarianism in the current Brazilian situation.